Design now ! - Fiell, Charlotte, 1965-; Fiell, Peter, 1958- (Hong Kong : Taschen, 2007)
Designs for life: From eco-design to design-art Not only an in-depth exploration of contemporary design practice, this book is also a rallying call for a more sustainable approach to product design of every type, from lighting and furniture design to consumer electronic equipment, transportation, product architecture, and environmental design. Visually stunning and highly informative, Design Now! illustrates the latest work by 90 of the world's leading designers and design-led manufacturing companies, while also featuring in-their-own-words statements that give a unique insight into the nature of 3-dimensional design today. Additionally, the editors? introductory essay authoritatively outlines the main issues facing designers, manufacturers and consumers, and offers a perceptive vision for a better way forward that focuses on the need to reduce, reuse, and recycle. Design Now! is essential for anyone interested in design and the road towards a greener future. Examples of selected designers and design-led companies featured: Ronan & Erwan Bouroullec, Ecotricity, Naoto Fukasawa, Zaha Hadid, Intelligent Energy, Jonathan Ive & Apple Design, LOT-EK, Ross Lovegrove, Marine Current Turbines, Jasper Morrison, Marc Newson, POC, Philips Design, Seymourpowell, Tokujin Yoshioka
Keywords: Ontwerpen